STUDI PENURUNAN KONSENTRASI KHROMIUM DAN TEMBAGA DALAM PENGOLAHAN LIMBAH CAIR ELEKTROPLATING ARTIFICIAL DENGAN METODE ELEKTROKOAGULASI - Dewi Masita; Ganjar Samudro; Dwi Siwi Handayani (Departemen Teknik Lingkungan Fakultas Teknik Universitas Diponegoro, 2013)
Electroplating industries produce wastewater containing heavy metals such as copper and chromium that can pollute the environment because they are toxic and harmful to human health despite a small quantity. However, they require a wastewater treatment that could decrease heavy metal waste. Electrocoagulation is the selected method because it has high ability to treat heavy metals wastewater and the equipment is simply enough. The experiments were conducted with artificial wastewater with varying concentrations of Cr 30, 40 and 50 mg/ l and Cu respectively 50, 100 and 200 mg/l. This study used an electrode type Aluminum (Al) that had distance 1.5 cm each electrode, 5 ampere current strength, sampling time every 30 minutes, time operation 360 minutes with an electrode washing every 120 minutes. From the experimental result had been obtained the best efficiency to reduce Cr and Cu occurred in minute 120 which up to 97 %. Aluminum electrode having saturation began at minute 270.